A Progressive Islamic Education Perspective on Calculus Learning Object and Media Innovation - Surur, Agus Miftakus; Tsani, Iskandar; Ridhwan, Mokhamad; Kuswandi, Dedi; Chuquin, Ector Geovanny Pupiales (Didaktika Religia, 2025)
This article examines the role of learning strategy objects and digital media in calculus instruction within Islamic higher education institutions. The main problem addressed is the low level of student engagement in understanding abstract calculus concepts and the suboptimal use of contextual and interactive learning objects. This research uses a qualitative method with a literature review approach. Data were analyzed descriptively and analytically to explore the function of media, learning objects, and technological innovations in facilitating students' comprehension of limits, derivatives, and integrals. The findings reveal that using instructional objects integrated with technology-based media, such as interactive simulations, concept visualizations through calculus applications, and contextual approaches grounded in Islamic values, enhances students’ conceptual understanding, active engagement, and learning motivation. The study recommends the development of calculus learning media tailored to the context of Muslim learners and the integration of spiritual values into instructional content and methods as part of a progressive Islamic education paradigm.